Pembinaan kelompok pembudidaya ikan melalui kegiatan diversifikasi produk olahan hasil budidaya ikan Lele di Kelurahan Tangkerang Utara Kota Pekanbaru - Iesje Lukistyowati; Niken Ayu Pamungkas; Adelina Adelina; Mulyadi Mulyadi; Indra Suharman (Unri Conference Series: Community Engagement, 2021)
The main problem faced by catfish farmers in North Tangkerang Village is that the market of catfish is only in fresh form, so that when the catfish harvesting activities is abundant, the price of fish decreases. The solution to overcome this was by conducting training activities for the PKK group of North Tangkerang Village, about the processing techniques of catfish cultured products into crackers and catfish nuggets. This service activity goes through three stages in the form of lectures on processed fish product innovations, processed product manufacturing practices, process evaluation and knowledge improvement evaluation. The results of the evaluation of the process and increasing knowledge of the implementation of the training activities carried out showed that during practice all extension participants were directly involved at each stage carried out and seemed enthusiastic in following each stage of the activities. After the training activities, all participants were able to independently make the technique of making catfish crackers and nuggets. Increased knowledge and skills of training participants by 81%. In general (79%) strongly agree with the implementation of this activity and 21% agree. The impact of this activity is expected to be an alternative source of income for the PKK group in this village and can continue in the future because of the assistance in the form of equipment for the processed production from the UNRI LPPM ABDIMAS TEAM.